Factors affecting reproductive traits in male snow leopards (Unciauncia). Issue 1 (11th November 2020) - Herrick, Jason R; Iske, Cayla J; Santymire, Rachel M; Lynch, Colleen; Alonge, Mattina; Krisher, Rebecca L; Morris, Cheryl L
Abstract : Abstract: The population of snow leopards ( Unciauncia ) maintained in US zoos is no longer sustainable due to poor reproductive success. Our objective was to assess reproductive traits in male snow leopards and identify factors (markers of oxidative stress in seminal fluid, surveys of husbandry practices, gonadal and adrenocortical activity, dietary intake of various nutrients, and genetics) that may affect ejaculate traits and subsequent fertility. Ejaculates (2.9 ± 0.2 mL) from 32 male snow leopards (9.8 ± 0.7 years; 38.6 ± 0.8 kg) housed at 27 institutions contained 119.2 + 26.0 x 10 6 spermatozoa, of which 75.1 ± 2.3% were motile and 28.6 ± 2.6% exhibited normal morphology. Overall, 34% of males produced <5 million spermatozoa and 27% of males produced spermatozoa with <20% normal morphology. Activity of superoxide dismutase (SOD) in the seminal fluid was negatively correlated ( P < 0.05, r 2 = 0.90) with normal sperm morphology. Husbandry practices, mean concentrations of fecal androgen metabolites (fAM), and baseline concentrations of fecal glucocorticoid metabolites (fGM), inbreeding coefficients, and generations each male was removed from the founders in their lineages were not correlated ( P > 0.05) with the total number of spermatozoa or the proportion of spermatozoa with normal morphology. Total sperm count was positively correlated ( P < 0.05, R 2 = 0.86) with the weekly intake of polyunsaturated fatty acids (PUFA) and the proportion of spermatozoa with normal morphology tended ( P < 0.10, R 2 = 0.31) to be positively correlated with copper intake. Altering the nutrient composition of snow leopard diets could provide managers with a possible method of improving reproductive traits in this endangered species. Lay summary: The population of snow leopards ( Uncia uncia ) maintained in US zoos has been declining since 1993 due to poor breeding success. Our objective was to assess the reproductive traits of male snow leopards and identify factors (e.g. hormones, diet, genetics) that may be affecting the quality of semen produced and therefore subsequent fertility. Within a cohort of 32 male snow leopards maintained at 27 US zoos, we found that 34% produced less than 5 million sperm and 27% of males produced sperm where less than 20% looked normal. The quantity and quality of the recovered sperm was not correlated with husbandry practices, concentrations of hormones (androgens and glucocorticoids) in feces, or genetics. However, the number of sperm was positively correlated with polyunsaturated fatty acids in the diet. Altering the nutrient composition of snow leopard diets could provide managers with a possible method of improving reproductive traits in this endangered species.